The Dynamic Macroeconomic Effects of Tax Policy in an Overlapping Generations Model - Heijdra, Ben (IMF Working Papers; Working Paper ;, 1998)
The paper studies the dynamic allocation effects of tax policy in the context of an overlapping generations model of the Blanchard-Yaari type. The model is extended to allow for endogenous labor supply and three tax instruments: a capital income tax, labor income tax, and consumption tax. Analytical expressions and simple diagrams are used to discuss the impact, transition, and long-run effects of tax policy changes. It is shown that a part of the long-run incidence of capital and consumption taxes falls on capital when households' horizons are finite, whereas labor would fully bear the burden of these taxes in an infinite horizon model.